2007
DOI: 10.1007/s00520-007-0332-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of end-of-life treatment for cancer patients in general wards and the palliative care unit at a regional cancer center in Japan: a retrospective chart review

Abstract: We found that families, not patients, consented to DNR, and life-sustaining treatments were appropriately withheld; however, patients on general wards received excessive hydration, and the use of palliative care drugs could be improved. Application of our findings can be used to improve clinical care in general wards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 39 publications
(58 reference statements)
4
39
1
1
Order By: Relevance
“…In addition, we showed that only 11% of patients in general wards were involved in consenting to DNR orders. This rate is similar to that reported in a previous study in Japan [9], suggesting that Japanese patients participate in decisions regarding their own DNR orders at a much lower rate (<5%) than patients in Western countries (19-68%) [19][20][21]. This lower rate seems to confirm that in Japan, end-of-life decision making is more often entrusted to families than to patients [22].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, we showed that only 11% of patients in general wards were involved in consenting to DNR orders. This rate is similar to that reported in a previous study in Japan [9], suggesting that Japanese patients participate in decisions regarding their own DNR orders at a much lower rate (<5%) than patients in Western countries (19-68%) [19][20][21]. This lower rate seems to confirm that in Japan, end-of-life decision making is more often entrusted to families than to patients [22].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, a prospective study produced similar findings of 40% and 23%, respectively [14]. Conversely, a retrospective study with a heterogeneous sample of patients in Japan reported that chemotherapy within the last 2 weeks of life was given to 5.8% of patients in general wards [9]. Although direct comparisons of those reports with the percentages in our study (25%) are difficult due to differences in setting and Patients are unlikely to benefit from chemotherapy when standard regimens have already failed.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The results of this study suggest that healthcare professionals in general wards could improve their practices about palliative care by learning about the standards of care in PCUs. First, large volume artificial hydration therapy may be still routinely given to terminally ill patients on general wards despite the potential risks such as aggravating ascites and pleural effusion [8] and lack of evidence that it improves patients' general well-being [4,9]. Because clinicians believe that intravenous hydration is the minimum standard of care and may be effective for symptom palliation [10], dissemination and education regarding guidelines for artificial hydration therapy for terminally ill patients could further improve the clinical practice of artificial hydration therapy on general wards [9].…”
Section: Discussionmentioning
confidence: 99%
“…Providing quality palliative care on a general hospital ward is therefore important for maintaining and improving the quality of life of terminally ill cancer patients across the country. Unfortunately, however, several surveys in hospital settings have suggested that many patients on general wards were highly distressed at the end of life due to inadequate symptom management and psychosocial support [2][3][4].…”
Section: Introductionmentioning
confidence: 99%